Characterization and Antifungal Activity of Silver Nanoparticles Mediated by Fungi (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Nanotechnology is quickly becoming one of the most essential and transformative areas of science. Physical, chemical, mechanical, and biological approaches are all used to create nanoparticles. Plants or microorganisms are frequently used in biological methods of metal ion reduction because they are clean, nontoxic, safe, biocompatible, and ecologically friendly. Fourir transform infra-red spectroscopy (FT–IR), scaning electron microscopy (SEM), and X-ray diffraction spectroscopy were described to analyze the nanoparticles generated (XRD). Nanoparticles (NPs) made from fungi have a diverse range of bio catalytic techniques, including enzyme immobilization for increased enzymatic activity. Silver (Ag) NPs made from fungi were discovered to have a benign effect in a wound and a thermal wound, and to have anti-mosquito, antibacterial, and antifungal properties